A Call For Concern In Global Warming In Jostein Gaarder's The World According to Anna Novel (2015): A Sociological Perspective - Nisa, Kamilatun; , Dr. M. Thoyibi, M.S (2017)
This study is about A Call For Concern in Global Warming in Jostein Gaarder's The World According to Anna (2015) which is analyzed by using sociological approach. The objectives of this study are to know indicators and impact of global warming in the novel, to know depiction of a call for concern in global warming in the novel, to know the reason why Jostein Gaarder addressed a call for concern in global warming in the novel. This novel belongs to qualitative research. The primary data source of this study is novel entitled The World According to Anna. Secondary data sources are the books, journals, internet and other sources that support the analysis. The findings of this research are as following. First, there are three indicators of global warming and four impacts of global warming. Three indicators of global warming are rising temperature, sea level, and melting ice and snow. Four impacts of global warming are environmental degradation, climate change, decreasing food and destruction of natural ecosystem. Second, a call for concern in global warming is depicted in the novel through the characters, setting, events and diction. The last is the reason why Jostein Gaarder addressed a call for concern in global warming in his novel such as to reveal the dangerous of global warming, to invite the reader to concern with global warming, to convey a message to the readers to start saving environment and reducing activities that can damage earth.